2017
DOI: 10.1200/jco.2017.35.15_suppl.e18148
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mild left ventricular dysfunction on trastuzumab use and oncologic outcomes in early stage breast cancer therapy.

Abstract: e18148 Background: Trastuzumab (T) significantly reduces the risk of breast cancer recurrence, but may be associated with an increased incidence of heart failure. The intention of this study was to assess how T therapy was managed after the development of mild left ventricular ejection fraction (LVEF) drop in a non-trial setting and to evaluate the cardiovascular and oncologic outcomes. Methods: Patients (pts) who received adjuvant T therapy in British Columbia for breast cancer between September 2005 and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Early discontinuation was associated with higher cancer recurrence. Similar results were revealed in a retrospective chart re- view of 2401 patients, in whom there was nearly a three-fold increase in risk of breast cancer recurrence if they had had an interruption in the course of trastuzumab treatment (17.5% vs. 6.3%) [27].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Early discontinuation was associated with higher cancer recurrence. Similar results were revealed in a retrospective chart re- view of 2401 patients, in whom there was nearly a three-fold increase in risk of breast cancer recurrence if they had had an interruption in the course of trastuzumab treatment (17.5% vs. 6.3%) [27].…”
Section: Discussionsupporting
confidence: 76%
“…One retrospective study showed that 5 years after the completion of breast cancer treatment 12% of women who had received trastuzumab alone and over 20% who had received trastuzumab following anthracyclines were diagnosed with heart failure or cardiomyopathy [13]. In another retrospective analysis from Denmark, 5 years after trastuzumab completion the risk of heart failure development among patients treated with chemotherapy-plus-trastuzumab compared with those treated with chemotherapy alone increased two-fold [27]. In one prospective observation heart remodelling (left ventricle and left atrium enlargement) was found in a substantial number of women 6 months after the completion of BC chemotherapy consisting of anthracyclines and trastuzumab [21].…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that regardless of the optimal target duration of trastuzumab, interruptions of therapy may be associated with poorer outcomes. A retrospective chart review of 2,401 patients aiming to complete 17 cycles of trastuzumab showed that there was nearly a 3‐fold increase in risk of breast cancer recurrence (17.5% vs. 6.25%) in patients who had an interruption in their course of treatment compared with those who did not . Ultimately, the risk of cardiotoxicity must be weighed against the survival benefits associated with continuing trastuzumab at the level of each individual patient.…”
Section: Trastuzumab Is a Highly Effective Treatment For Her2‐positivmentioning
confidence: 99%